2005
DOI: 10.1063/1.1849828
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman scattering from undoped and phosphorous-doped (111) homoepitaxial diamond films: Stress imaging of cracks

Abstract: We report postgrowth micro-Raman stress imaging of cracks in ͑111͒ homoepitaxial diamond films. Undoped and phosphorous-doped diamond thin films grown by microwave plasma-enhanced chemical-vapor deposition on Ib ͑111͒-oriented diamond substrates have been studied by confocal micro-Raman spectroscopy. For comparison purposes, a film grown on a ͑100͒ Ib substrate was also examined. Thanks to the confocal optics, the Raman signal arising from the epilayer could be discriminated from that arising from the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Under the uniaxial lattice strain, the triply degenerate first‐order vibrational mode splits into singlet and doublet components . For single‐crystal homoepitaxy, the similar peak splitting was reported for heavily phosphorus incorporations . This mode splitting is observable for W concentration above 10 18 cm −3 for our experimental conditions.…”
Section: Mechanism Underlying Dislocation Annihilation By Matsupporting
confidence: 84%
“…Under the uniaxial lattice strain, the triply degenerate first‐order vibrational mode splits into singlet and doublet components . For single‐crystal homoepitaxy, the similar peak splitting was reported for heavily phosphorus incorporations . This mode splitting is observable for W concentration above 10 18 cm −3 for our experimental conditions.…”
Section: Mechanism Underlying Dislocation Annihilation By Matsupporting
confidence: 84%
“…At this point the observed blueshift cannot be explained. Commonly redshifts due to tensile stress in micro‐ and single crystalline P‐doped diamond layers have been reported . Overall, both samples feature an excellent film quality.…”
Section: Resultsmentioning
confidence: 99%
“…So a large Raman peak shift is not exclusive to CVD diamond. For example, Mermoux et al 41 observed the peak shift down to 1326.2 cm −1 for epitaxial films on (111)-oriented substrates and assigned it to an enhanced concentration of defects in this plane. Using the pressure coefficient obtained for a GeV ZPL energy of d E /d p = 3.29 meV GPa −1 , 42 we estimate the stress-induced ZPL shift of 8.39 meV (67.7 cm −1 ), moving the peak from 602 nm to 604.4 nm in excellent agreement with the measured GeV position.…”
Section: Resultsmentioning
confidence: 99%